Does Energy Diversification Cause an Economic Slowdown? Evidence from a Newly Constructed Energy Diversification Index - Giray Gozgor; Sudharshan Reddy Paramati (Center for Economic Studies and ifo Institute (CESifo), 2021)
Countries have made considerable efforts to diversify their energy sources from fossil fuels to renewables in the last two decades to achieve sustainable economic development. However, it is widely argued that the countries may experience sluggish economic development during the energy transition period due to structural and functional changes in the economic system. Given this backdrop, this study introduces a new measure of energy diversification. It explores its impact on economic development across the panels of low-income, high-income, European Union (EU), the Organization for Economic Co-operation and Development (OECD), and G20 countries. The study uses data from 1995 to 2018 and utilizes Nonlinear Panel Autoregressive Distributed Lag (NPARDL) method. Our findings confirm that the major economies (including G20) realize positive economic growth with increasing long-run energy diversification. However, some countries (OECD and G20) experience negative economic growth due to energy diversification in the short term. The results also disclosed that energy diversification does not favor economic growth in low-income economies in both the short and long term. Therefore, more precautionary measures to be taken into account while diversifying energy sources.
Keywords: O47; Q01; Q42; 330; energy diversification; energy transition; energy mix; economic development; climate change; nonlinear panel ARDL estimations